2021
DOI: 10.1007/s40519-021-01220-6
|View full text |Cite
|
Sign up to set email alerts
|

Food and alcohol disturbance among young adults during the COVID-19 lockdown in Italy: risk and protective factors

Abstract: Purpose The COVID-19 lockdown measures have had a significant impact on risk behaviors as alcohol use and disordered eating. However, little is known about a serious health-risk-behavior named “food and alcohol disturbance” (FAD), characterized by engaging in dysfunctional eating on days of planned alcohol consumption. The aim of the present study was to investigate potential factors that may have put young adults at risk or protected against FAD during the COVID-19 lockdown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
(94 reference statements)
1
10
0
Order By: Relevance
“…These correlations are consistent with the existing literature about trauma in EDs, the hypothesis being that they might be a mental escape from negative affects [49]. Interestingly, these data have been reported by different population studies as effects of the COVID-19 pandemic, even in the general population [50,51]. Moreover, while these elements have already been classified as fundamental by trauma-informed treatments, there is still work to be done in their integration into evidence-based treatments [52].…”
Section: Discussionsupporting
confidence: 88%
“…These correlations are consistent with the existing literature about trauma in EDs, the hypothesis being that they might be a mental escape from negative affects [49]. Interestingly, these data have been reported by different population studies as effects of the COVID-19 pandemic, even in the general population [50,51]. Moreover, while these elements have already been classified as fundamental by trauma-informed treatments, there is still work to be done in their integration into evidence-based treatments [52].…”
Section: Discussionsupporting
confidence: 88%
“…On this subscale, questions investigate the frequency with which compensatory behaviors are engaged around alcohol consumption episodes, with answers rated on a Likert-type scale ranging from 1 ( never ) to 5 ( always ). The DMBS has been shown to have good psychometric properties in the Italian context [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the present study, the instrument showed high reliability (Cronbach’s alpha = 0.97).…”
Section: Methodsmentioning
confidence: 99%
“…These emotional issues may have had cascade effects on health risk behaviors, increasing the likelihood that young adults would develop alcohol-related problems and dysfunctional eating patterns, such as those associated with drunkorexia. The long-term psychological impact of the COVID-19 pandemic on drunkorexia behaviors has not yet been studied, despite recent evidence that maladaptive emotion regulation strategies significantly predicted drunkorexia behaviors during the lockdown [ 11 ]. Moreover, a trend of increased alcohol use during the pandemic [ 12 , 13 ] highlights the need to identify COVID-19–specific distress factors associated with alcohol abuse in order to better prevent and monitor these behaviors in the post-pandemic phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is important to use scientific method to ask questions around this and quantify it, we do have to challenge whether this is useful science. A literature review shows that more than 150 papers were published on Covid-19 lockdown weight gain [6][7][8][9] and twice that number on changes in food intake. [10][11][12] Although these studies covered a wide range of population groups (Figure 1), they collectively reached the entirely obvious conclusion that pandemic restrictions were not conducive to the promotion of healthy lifestyles.…”
Section: Keeping Originality In Focusmentioning
confidence: 99%